2015
DOI: 10.1016/j.bone.2015.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between bone geometry, volumetric bone mineral density and bone microarchitecture of the distal radius and tibia with alcohol consumption

Abstract: Relationships between bone geometry, volumetric bone mineral density and bone microarchitecture of the distal radius and tibia with alcohol consumption, Bone (2015), doi: 10.1016/j.bone. 2015.05.002 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 39 publications
0
15
1
Order By: Relevance
“…Unfortunately, no routine, noninvasive method for evaluating bone in humans provides insight into bone quality. However, a recent study evaluated the relationship between current alcohol consumption and bone in the distal radius and tibia in aged men and women using high‐resolution computed tomography (Paccou et al., ). Moderate to heavy alcohol consumption was associated with minimal changes in bone geometry, density, and microarchitecture.…”
Section: Alcohol and Bonementioning
confidence: 99%
“…Unfortunately, no routine, noninvasive method for evaluating bone in humans provides insight into bone quality. However, a recent study evaluated the relationship between current alcohol consumption and bone in the distal radius and tibia in aged men and women using high‐resolution computed tomography (Paccou et al., ). Moderate to heavy alcohol consumption was associated with minimal changes in bone geometry, density, and microarchitecture.…”
Section: Alcohol and Bonementioning
confidence: 99%
“…Similarly, the highest aBMD was exhibited in postmenopausal women (mean 62.8 ages) who drank 2-3 times per week compared to the non-drinkers [19]. In terms of volumetric BMD (vBMD, g/cm 3 ) measured by high-resolution peripheral quantitative computed tomography, Paccou et al [17] found that men (mean 76.1 years) who consumed low amounts of alcohol had a lower vBMD, but women (mean 76.5 years) with moderate/high alcohol intake had a significantly higher vBMD. Our study did not find differences in aBMD of the lumbar spine, but lighter drinkers (1-9 g/day) exhibited higher aBMD of the lumbar spine in elderly women (50 to 79 years) compared to non-drinkers [16].…”
Section: Discussionmentioning
confidence: 96%
“…All of these factors can interplay to produce conflicting results on human skeletons. Unfortunately, most of the previous studies investigating the relationship between alcohol consumption and areal bone mineral density (aBMD) have focused on either middle-aged/older men and/or middle-aged/postmenopausal women [16][17][18][19][20]. Very few studies have examined the relationship between alcohol and bone in young adults [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Globally, it is one of the major causes of osteoporosis in men (Giusti & Bianchi, ; Kim et al, ; Misiorowski, ). Higher use has been shown to decrease BMD (Alvisa‐Negrín et al, ; Lairinen, Lamberg‐Allardt, Tunninen, Harkonen, & Valimaki, ; Malik et al, ; Maurel, Boisseau, Benhamou, & Jaffre, ; Paccou et al, ; Ulhøi, Meldgaard, Steiniche, Odgaard, & Vesterby, ), and increase the number of empty osteocyte lacunae (Maurel et al, ). With continued high consumption, men may be more susceptible to BMD decrements than their female counterparts (Kanis et al, ; Malik et al, ).…”
Section: Discussionmentioning
confidence: 99%